188 Structural differences in access to neurological healthcare in Northern Ireland: a neurodisparity index. Issue 6 (27th May 2022) - McCarron, Mark; Burns, Paul; Forbes, Raeburn; McCarron, Luke; Mcverry, Ferghal
Abstract : Disparities in management of neurological patients should be minimal in a universal healthcare system. Northern Ireland has one neuroscience centre but no neurology centres. We have devised an easily- applied neurodisparity index (NDI) to measure population equity of neurological healthcare. NDI=number of patients managed per 105 population per Trust/number of patients managed per 105 population of the tertiary centre Trust. NDIs <0.75 and >1.25 were arbitrarily designated as neurodisparities. NDIs were calculated between 2013–2016 for intravenous thrombolysis (eight centres) or mechanical thrombectomy (one centre) for acute ischaemic stroke (AIS), disease modifying drug use for multiple sclerosis (>10 centres) and admissions to a neuroscience neurology ward (n=1) to determine the source and extent of neurodisparity. Amalgamated NDIs for non-tertiary centre trusts were: 0.36 for mechanical thrombectomy for AIS; 0.79 for intravenous thrombolysis for AIS; 1.1 for disease modifying treatment for multiple sclerosis and 0.48 for patient admissions to the tertiary neurology ward. Individual Trust data demonstrated a geographical gradient for mechanical thrombectomy and regional ward admissions. Neurodisparities in Northern Ireland are most marked for mechanical thrombectomy and regional neurology ward admissions. Commissioners should be aware that geography and time-dependent man- agement can exacerbate neurodisparities. Extra resources are required to address such neurodisparities. markmccarron@doctors.org.uk